PENGARUH KARAKTERISTIK PEKERJAAN DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI DENGAN MEDIASI MOTIVASI (STUDY PADA SEKRETARIAT DAERAH KABUPATEN PATI) - Baharudin, 11.52.02.0042 (Students Journal of Economic and Management, 2013)
The purpose of this study to determine the effect of job Characteristic and Currier Development on performance mediated by the Motivation in Sekretariat Daerah Kabupaten Pati. This research was conducted with a purposive sampling method and implemented in Sekretariat Daerah Kabupaten Pati. Technical test data used in this study include validitas test, reliability test, multiple regression analysis, t test, and test the mediation hypothesis to test and prove the researchers. Tested the validity of data collected by looking at the magnitude of the KMO values ââabove 0.5 and the factor loading above 0.4 shall be declared invalid. The results demonstrate the validity of the KMO test for job characteristic is 0.885 with a loading factor between 0.527 â 0.880, KMO test for currier development is 0.873 with the loading factor between 0.511 â 0.844 KMO test for motivation 0.796 with the loading factor between 0.560 - 0.715 and KMO test for the performance is 0.853 with loading factor between 0.423 â 0.750 It can be said that all variables declared valid. Its reliability test showed the 0.869 for job characteristic, 0.868 for currier development, 0,846 for motivation and 0.886 for performance. This shows that all variables are reliable. From the analysis and discussion suggests that a significant positive influence job characteristic on motivation, significantly positive effect of currier development on motivationt, jib characteristic is a significant positive effect on performance, currir development significantly positive effect on performance and motivation significantly positive effect on performance. Strong influence of job characteristic is directly compared to the performance through the mediation of motivation. And Strong influence of currier development is directly compared to the performance through the mediation of motivation. Keywords: Job Characterics, Currier Development,Â Motivation and Employee Performance.